Copyright Royalty Regulation and Competition in the Music Retail Market - Yang, YongHyeon (2017)
Price control can restore efficiency in some cases, but an uncarefully designed policy fails to restore efficiency, yields side effects, or even exacerbates efficiency losses. This paper shows that the copyright royalty rule, which takes the greater of ad valorem royalties and perunit royalties, tends to fix the prices of final goods at a specific level. Such a rule weakens competition as it prevents prices from decreasing even when market conditions change, having negative effects on social welfare as well as consumer surplus. Counterfactual analyses using estimation results in the Korean online music service industry show that firms could have profitably reduced prices if the ad valorem rule had been applied instead, although they did not have an incentive to do so under the original combination rule.